Analisis Perbedaan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering - Diyah Permana; Noktah Tri Marwardika (Politeknik Negeri Samarinda, 2022)
This research aims to distinguish whether there is a significant difference between the company's financial performance before and after conducting an Initial Public Offering (IPO) on the Indonesia Stock Exchange judging by the Current Ratio, Total Assets Turnover, Debt to Equity Ratio, and Return on Investment. The population of this study is the company that conducted the Initial Public Offering on the Indonesia Stock Exchange in 2017 with a sample of 31 non-financial companies taken by purposive sampling. The data collection techniques in this study use documentation techniques. Data analysis techniques are carried out by describing the financial data of the sample company, namely the financial ratio of the period three years before and three years after the Initial Public Offering, which is to use descriptive statistics. The results showed that: there is a significant difference between the company's financial performance before and after the Initial Public Offering (IPO) in 2014-2020 on the Indonesia Stock Exchange both in liquidity ratio, activity ratio, profitability ratio and solvency ratio.